Temporal Expressions in English and Spanish: Influence of Typology and Metaphorical Construal - Valenzuela, Javier; Alcaraz Carrión, Daniel (Frontiers in Psychology, 2020)
This study investigates how typological and metaphorical construal differences may affect the use and frequency of temporal expressions in English and Spanish. More precisely, we explore whether there are any differences between English, a satellite-framed language, and Spanish, a verb-framed language, in the use of certain temporal linguistic expressions that include a spatial, deictic component (Deictic Time), a purely temporal relation between two events (Sequential Time) or the expression of the duration of an event (Duration). To achieve this, we perform two different types of analysis. First, we conduct an informational gain or loss analysis (Verkerk, 2013) of 1,650 of English-to-Spanish translations extracted from parallel corpora. Secondly, we compare the frequency of 33 English and 27 Spanish temporal expressions in two similar written online corpora (EnTenTen and EsTenTen, respectively) and a television news spoken corpus (NewsScape). Our results suggest that English uses “deictic directional expressions” (explicitly stating the spatial location of the temporal event,, e.g., back in those days/in the future ahead) much more frequently than Spanish, to the extent that directional information is normally excluded in English-to-Spanish translations. Also, sequential expressions (such as before that/later than) and duration expressions (during the whole day) are much more frequent in Spanish. These usage differences, explained by the variability in motion typology and metaphoric construal, open up the interesting question of how these differences in linguistic usage could affect the conceptualization of time of English and Spanish speakers.